1993
DOI: 10.1038/ki.1993.341
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction and focal contact formation indicate integrin expression in mesangial cells

Abstract: Cultured kidney glomerular mesangial cells (MCs) allow the role of extracellular matrix (ECM) and growth factors in glomerular inflammatory disease to be studied. To investigate the potential of MCs to interact with matrix components, the expression of integrin mRNA in cultured MCs was examined by polymerase chain reaction (PCR), by Northern blotting and by immunofluorescence. In addition, the effect of matrix substrates on mRNA expression was assessed by PCR. Northern blots with cDNA probes to integrin alpha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Mesangial cells have been found to express the integrin a subunits, al-3, a5 and d. All these a subunits combine with pl (Petermann et al, 1993). In addition, we found that the integrins expressed by mesangial cells include avp5 and m p 6 in vivo, and avp3 and avp5 in vitro.…”
Section: Integrins and Integrin Subunitsmentioning
confidence: 49%
“…Mesangial cells have been found to express the integrin a subunits, al-3, a5 and d. All these a subunits combine with pl (Petermann et al, 1993). In addition, we found that the integrins expressed by mesangial cells include avp5 and m p 6 in vivo, and avp3 and avp5 in vitro.…”
Section: Integrins and Integrin Subunitsmentioning
confidence: 49%
“…It has been suggested that structures resembling focal contacts exist between mesangial cells and GBM both in vivo and in cultured mesangial cells [24,32]. This is thought to mean that any alterations in these contacts will alter the regulatory action of mesangial cells on glomerular haemodynamics [9].…”
mentioning
confidence: 98%
“…In addition, the β 1 integrins α 3 and α 5 as well as α v β 3 are observed on parietal and visceral epithelial cells. Cultured human and rat MCs express α 1 , α 2 , α 3 A, α 5 , α 8 , α v , β 1 , β 3 , β 5 and weakly α 6 at mRNA and protein levels [2, 8, 9, 10, 11, 12, 13, 14](table 1). In general, the integrin expression pattern of cultured MCs is comparable to that observed in renal tissue sections.…”
Section: Mesangial Ecm and Receptors In Normal Glomeruli And Culturedmentioning
confidence: 99%
“…As anchorage-dependent cells, MCs in culture form focal contacts. Immunocytochemical analysis of rat and human MCs in culture revealed that β 1 , α 1 , α 3 , α 5 , α 8 and α v can be organized in focal adhesions [13, 14](fig. 2).…”
Section: Regulation Of MC Adhesionmentioning
confidence: 99%
See 1 more Smart Citation